Using separation of concerns for embedded systems design - Jackson, Ethan; Sztipanovits, Janos (EMSOFT '05 Proceedings of the 5th ACM international conference on Embedded software, 2005)
Embedded systems are commonly abstracted as collections of interacting components. This perspective has lead to the insight that component behaviors can be defined separately from admissible component interactions. We show that this separation of concerns does not imply that component behaviors can be defined in isolation from their envisioned interaction models. We argue that a type of behavior/interaction co-design must be employed to successfully leverage the separation of these concerns. We present formal techniques for accomplishing this co-design and describe tools that implement these formalisms.